Critical factors of success in the digital trade of the Costa Rican exporting SMES - Vásquez Esquivel, Ivonne (2019)
The purpose of this research is to evaluate the current situation of electronic commerce (EC) in the Costa Rican export Micro, Small, and Medium Enterprise (MSMEs), in terms of (1) technological elements and information used in the web site, (2) the companies’ perception on what factors they consider critical for its implementation. At least 82 companies were identified with an EC site, out of a total of 2,849 companies that make up the export business park in 2014 and 2015. These EC sites were analyzed to identify the technological and information elements present in each one. A survey was applied to their managers to identify their perception about which factors, from a list of options, they consider critical for the success of their commercial activities over the Internet. The analysis of the websites shows a medium or poor quality in most of them. The success factors identified reflect a knowledge of the exporting MSMEs about the substantive activities of this type of marketing, being considered important by more than 90% of these companies the "customer orientation" of the site and the "privacy of the information"; and for more than 65% of MSMEs, the ease of use and constant updating of the site, its availability 24/7, the after-sales service and the delivery time, the reputation of the company and the type of product.